Thematic trends in industry 4.0 revolution potential towards sustainability in the construction industry - Mohd Zairul; Zaremohzzabieh, Zeinab (Multidisciplinary Digital Publishing Institute, 2023)
The construction industry is currently facing challenges because of the massive waste generated by its production processes. The climate agreement also requires the industry to meet the increasing demand for sustainable building materials to achieve the energy transition. As a result, the construction industry is looking for alternative ways to meet these sustainability challenges. The implementation of the fourth industrial revolution (IR4.0) can be an opportunity for the construction industry to become more sustainable. Therefore, this paper aims to (i) ensure a detailed assessment of the existing challenges and (ii) identify the potential implementation of IR4.0 technologies in the construction industry. A set of criteria was established for searching and screening papers from three major databases (Scopus, WoS, and Mendeley), and 58 eligible articles were included in the current study. Using ATLAS.ti 22 software, a thematic analysis was conducted, and the final six themes were determined based on problems and challenges, technology and tools, information technology, consulting and business, construction management, and education. In addition, this paper identified potential prospective study paths. It is expected that the results will be useful for the future direction of the industry in addressing the challenges of IR4.0.